TASK-BASED INSTRUCTION FOR ENGLISH YOUNG LEARNER CLASSROOM - Fera Sulastri; Neni Marlina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: As the development of globalization era, teaching English for young learner regarded as a preparation for a future generation to face it. The children regarded as the future generation are already enrolled in an English class in their early ages. Within their unique characters, the way of teaching and learning process is different from what the adults got. Task-Based Instruction, as one of the new method of communicative approach, has been used as an effective way in teaching a foreign language, especially for adult learners. The issue comes by its implementation into young learners. It is said to be a doubtful thing to apply Task-Based Instruction into young learners in learning foreign language. The characteristics of Task-Based Instruction which includes three stages; (1) Pre-Task, (2) Task-Cycle, (3) Language focus is regarded to be too much for young learners. Bedsides, it is said that implementing Task-Based in English young learner classroom can be a burden for them. Beginning by this perception, this study investigates; (1) the implementation of Task-Based Instruction in English young learner classroom (2) some adaptation that can be done in using Task-Based Instruction for young learner (3) the strengths and weaknesses of Task-Based Instruction in English Young Learner Classroom.Keywords: Task-Based Instruction, pre-task, task-cycle, young Learners